Carpochron: a concept for the time interval between the appearance of fruits in consecutive harvests - Schoffel, André; Koefender, Jana; Golle, Diego Pascoal; Camera, Juliane Nocolodi (Comunicata Scientiae, 2024)
The aim of this research was to estimate the base temperature for the appearance of fruits at harvest point in the strawberry and to propose a concept to represent the time required for the appearance of fruits in consecutive harvests. The experiment was conducted in 2021 in four seedling transplanting seasons: May (season 1), June (season 2), July (season 3) and August (season 4) of two cultivars: Fronteras and Merced. Twenty-four consecutive fruit harvests were carried out from September 9, 2021, to December 1, 2021, when the number, length (cm), diameter (mm), and fresh weight of the fruits (g) were evaluated. The base temperature for the fruit emission of the strawberry was calculated using the method of the smallest mean square error. Carpochron was estimated at each season and for each cultivar, obtaining a simple linear regression between the number of fruits and the accumulated thermal sum (ºC day) and the number of days after transplanting (DAT), using as base temperature the one estimated in this work. The base temperature for the appearance of consecutive fruits at the harvest point in the strawberry is 11ºC. Carpochron increases with the delay of the transplanting season and the values ranged from 81.97ºC fruit day to 144.93ºC fruit day for cultivars Merced and Fronteras.